(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Role of Social Capital in Preserving Subak Pinjinan in the Village of Kedis, Busungbiu Sub-district, Buleleng Regency. Subak Pinjinan is one of the Subak located in Buleleng Regency that still exists. This subak is located in Kedis Village, Busungbiu District, Buleleng Regency. It is well known that many subak in Bali have experienced some issues in the conversion of land functions, which also happened in Subak Pinjinan. Subak Pinjinan was previously 50 Ha and now decreased into 25 Ha. The purpose of this research is to find out how the social capital which consists of three components: believe, norms, and networks, plays a roles in preserving Subak Pinjinan. The location of this research is chosen purposively because this subak is one of the subak that still exists in the middle of the on going land conversion problem, while similar research has been done at Subak Pinjinan. The analytical method used in this research is descriptive qualitative and uses a sample of 62 active members of Subak Pinjinan. The results of this research indicate that the social capital owned by Subak Pinjinan is good, this can be proved by: (1) The members have mutual trust between each others, they also built a good trust in subak administrators, they have confidence in government programs, and they believe in religious rituals. (2) Subak norms and values have been complied with and implemented well by all members of the Subak Pinjinan, except they have to comply the awig-awig regarding land conversion. (3) the social network between the subak and the government of Kedis Village, and the other relevant governments has been running well. The advice that can be given by this research, is that the government needs to strictly apply the regulations and to not hesitate giving any penalty regarding the issues of land conversion. It also requires awareness from all farmers to not do any kind of things that leads to a land conversion.